2022
DOI: 10.1177/00219983221136073
|View full text |Cite
|
Sign up to set email alerts
|

A novel natural fiber from plane tree (Platanus orientalis L.) fruits to reinforce polypropylene composites

Abstract: This study investigated the mechanical properties of polypropylene composites reinforced with short natural fibers obtained from plane tree ( Platanus orientalis L.) fruits. The fibers were harvested from the fruits that naturally fell from the tree in their standard length of about 6 mm. Composites were produced via melt blending using varied concentrations of the fibers (5–10–20–30 wt.%) and maleic anhydride grafted polypropylene (MAPP) copolymer as the coupling agent. The mechanical properties of the compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The plane tree is a large deciduous tree with a very thick and short trunk that spreads thick and long branches upward and to the sides. It grows to a height of about 30–50 m and a diameter of 1–2.5 m [ 1 , 2 ]. Older trunks have deeply fractured bark that is covered in tiny scales that do not fall off over time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plane tree is a large deciduous tree with a very thick and short trunk that spreads thick and long branches upward and to the sides. It grows to a height of about 30–50 m and a diameter of 1–2.5 m [ 1 , 2 ]. Older trunks have deeply fractured bark that is covered in tiny scales that do not fall off over time.…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies reported on the creation of a dye removal adsorbent and solar evaporator by utilizing 3D spherical carbonized fibers and fruits [ 13 , 14 ]. By using short natural fibers from plane tree ( Platanus orientalis L.) fruits, Atabek Savas 2022 [ 2 ] examined the mechanical characteristics of polypropylene composites. Moreover, it is possible to utilize numerical methods to evaluate the mechanical performance of the new extracted fibers in the literature [ 15 ] instead of time-consuming and expensive experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural fibers have been largely studied as reinforcement in polymer composites. [1][2][3][4] Advantages related to the wide variety of plants that can provide fiber, renewable and environmentally friendly source of raw material, low cost for production and acceptable reinforcing properties for polymer composites can explain this trend. 5,6 Elephant grass or Napier grass (Pennisetum purpureum schum) is a plant originated from the African continent with fast growth, which can be found throughout the Brazilian territory.…”
Section: Introductionmentioning
confidence: 99%